2019
DOI: 10.21511/kpm.03(1).2019.03
|View full text |Cite
|
Sign up to set email alerts
|

The role of knowledge management in institutional strategy development and competitiveness at leading African universities

Abstract: The role of knowledge management as a strategic intervention in higher education in developing economies has not been studied extensively. Higher education plays a central role in a country’s economy through knowledge creation and dissemination to its stakeholders. The main purpose of this article was to examine the role and influence of knowledge management in decision-making and strategy formulation at leading universities in Africa and to establish if knowledge management was adding value and competitivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Simultaneously with the spread of intellectualization of the global economy and its active digitalization, knowledge is increasingly becoming important in achieving eco-The impact of ICT on economic growth has been confirmed at various hierarchical levels (Takhtravanchi, Pathirage, 2018;Bilan et al, 2019;Suknunan, Maharaj, 2019;Polyakov et al, 2020). The authors use data of correlation analysis and modeling of the impact of ICT factors on the main financial results and prove that sustainable socioeconomic growth has acquired the features of constant digital development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simultaneously with the spread of intellectualization of the global economy and its active digitalization, knowledge is increasingly becoming important in achieving eco-The impact of ICT on economic growth has been confirmed at various hierarchical levels (Takhtravanchi, Pathirage, 2018;Bilan et al, 2019;Suknunan, Maharaj, 2019;Polyakov et al, 2020). The authors use data of correlation analysis and modeling of the impact of ICT factors on the main financial results and prove that sustainable socioeconomic growth has acquired the features of constant digital development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, prior investigations have demonstrated that universities possess an inherent potential for cultivating attributes such as quality, innovation, and functionality. These focal attributes serve as the bedrock for well-established competitive advantages while effectively managing the knowledge generated in the institution's daily affairs (Sachin & Manoj, 2019). This phenomenon becomes exceedingly intriguing when observed in action.…”
Section: Knowledge Management and Competitiveness In Universitiesmentioning
confidence: 99%
“…KM is about leveraging the knowledge assets available to the organization to generate competitive advantage and innovation (Rehman et al , 2021a). Experts and knowledge creators may thrive in this competitive atmosphere, as it requires and encourages exchanging ideas (Andreeva and Kianto, 2012; Suknunan and Maharaj, 2019). Using a knowledge-based perspective, the essential means of production are intangible (e.g.…”
Section: Introductionmentioning
confidence: 99%